Mouse olfactory bulb methylome and hydroxymethylome maps reveal noncanonical active turnover of DNA methylation. Issue 8 (3rd August 2017) - Ma, Qin; Lu, Huan; Xu, Ziying; Zhou, Yuanyuan; Ci, Weimin
ABSTRACT: Hydroxylation of 5-methylcytosine (5mC) to 5-hydroxymethylcytosine (5hmC) by TET enzymes presents a particular regulatory mechanism in the mammalian brain. However, although methylation and hydroxymethylation of cytosines in non-CpG contexts have been reported, these mechanisms remain poorly understood. Here, we applied TAB-seq and oxBS-seq selectively to detect 5hmC and 5mC at base resolution in olfactory bulb derived from female mice. We found that active turnover of 5mC to 5hmC occurred in both CpG and non-CpG contexts. Strikingly, we identified a different sequence preference for 5mC and 5hmC in a CH context, in which H = A, C, or T, TNCA/TC for 5mC and NNCA/T/CN for 5hmC. More importantly, we found that genes showing 5mC to 5hmC turnover showed only limited overlap in CpG and CH contexts, and that olfactory receptor genes were marked with higher turnover of 5mC to 5hmC in non-CpG context. Collectively, we identified an unexpected sequence preference for non-CpG hydroxymethylation and distinct target genes regulated by the turnover of 5mC to 5hmC in CpG and CH contexts.